D4N2024 Presentation Showcase – THEMATIC SESSION 4b: Gender and Social Inclusion - Saville, Naomi; Banerjee, Archis; DuttaGupta, Tanaya; Alvi, Muzna; Jolly, Saira Parveen; Nguyen, Phuong Hong; Maringmei, Jasmine; Vaidya, Sneha; Pradhan, Mamata (International Food Policy Research Institute, 2024)
D4N2024 Presentation Showcase – THEMATIC SESSION 4b: Gender and Social Inclusion